IMPLEMENTATION OF THE INDEPENDENT LEARNING CURRICULUM IN THE COURSE OF CREED AND MORALS AT MADRASAH ALIYAH NEGERI 2 PASAMAN BARAT - Zukhroini; Iswandi, Iswandi; Rahmadi, Rahmadi; Fitria, Mita (Mandeh : Jurnal Pendidikan Islam, 2024)
This research was motivated by an observation at Madrasah Aliyah Negeri 2 Pasaman Barat, where it was found that Akidah Akhlak teachers faced various problems in implementing learning in accordance with the principles of the Independent Curriculum. The problems that emerged included low motivation and active participation of students in participating in learning, lack of interest in learning. One part of the implementation of the independent curriculum is to use various methods in learning to make learning more enjoyable, but in fact the Akidah Akhlak teachers at this madrasah have not used various methods, namely only using the lecture method like the previous curriculum which does not require students to be active in learning. The purpose of this study was to find out 1) How the implementation of the independent learning curriculum in the Learning Program Plan for the Akidah Akhlak subject at Madrasah Aliyah Negeri 2 Pasaman Barat 2) How the implementation of the independent curriculum in the implementation of learning in the Akidah Akhlak subject at Madrasah Aliyah Negeri 2 Pasaman Barat 3) How is the evaluation of learning regarding the implementation of the independent curriculum in the Akidah Akhlak subject at Madrasah Aliyah Negeri 2 Pasaman Barat. This research is a descriptive qualitative study using data collection methods through observation, interviews with teachers, and documentation of learning activities. The use of this method is expected to obtain concrete data according to the research needs. From the results of the study, the author found that the implementation of the Independent Learning Curriculum at Madrasah Aliyah Negeri 2 West Pasaman has been running effectively, so that to some extent the objectives of the Independent Learning Curriculum implementation have begun to experience progress in learning. However, teachers still experience obstacles in implementing learning, so teachers are required to innovate and the learning process is not entirely carried out in the classroom, making learning more varied and less boring.